Over a million students use our free study notes to help them with their homework
First label the equations. 1: 5x + 2y = 4 . 2: x - y - 5 = 0 . Rearrange equation 2 . 2: y = x - 5 Substitute equation 2 into equation 1 . 5x + 2( x - 5 ) = 4 . 7x = 14 . x = 2 . Substitute x = 2 into equ...
First note that a=eln(a) and ln(ab)=bln(a)By substituting a=3x we get a=3x=eln(3^x)=exln(3), and hence f(x)=exln(3)Answered by Christian C. • Maths tutor2631 Views
Put the equation in the form Rsin(x-a) (=Rsin(x)cos(a)-Rcos(x)sin(a)). Looking at the original equation Rcos(a) = 2 and Rsin(a) = 1.5. Tan(a)=1.5/2 and R^2= 2^2 +1.5^2. Therefore R = 2.5 and a = 0.6435.Th...
Write out the product rule: if y=f(x)g(x) where f and g are functions, dy/dx = f'(x)g(x) + f(x)g'(x)Substitute in the expressions from the question:Therefore if f(x)=cos(3x) and g(x) = cosec(5x), f'...
start of by expanding the braquet which has got a power(x + 2y) (x + 2y) = X2 + 2xy + 2xy + 4Y2then simplify that => x2 + 4xy + 4y2then multiply that by (x -...
←
686
687
688
689
690
→
Internet Safety
Payment Security
Cyber
Essentials